Intestinal Parasites Prevalence in Children from Day Care Centers in Sinop City-MT - B. Muchiutti; L. L. A. Lima; D. Gabriel; M. Escobar; F. M. P. Garcia; A. Lima (Scientific Electronic Archives, 2013)
Abstract: The aim of this study was to investigate the intestinal parasitosis prevalence of children from municipal day care centers in Sinop MT. Respecting ethical principles established by Resolution 196/96 of Health National Council/Ministry of Health of quantitative research, the anonymity of participants, as well accept and signature of parents of the Term of Free and Enlightened Consent were performed. Between Junes to October 2012 were applied coproparasitological methods for investigation. Fecal samples were analyzed by Hoffmans methods. From 103 students examined observed the prevalence rate of 19.42% of intestinal parasites. The intestinal parasites with highest prevalence rate were: Giardia lamblia (9.70%) and Endolimax nana (5.82%). The results of this study demonstrate the need for sensitization of the population front of diagnosis importance, treatment and monitoring of positive cases and the necessity of more health professionals attention, especially with children.